The Deformation Analysis of a Deep Frame Top-Down Excavation in Downtown Shanghai Based on the 3D FEM - Ting Bai (Hindawi Limited, 2021)
The deformation and environmental influence of the pit excavation in downtown is very important. A 3D FEM analysis is conducted to understand the deformation of a 13.9 to 15.2 m deep excavation with an in-plane dimension of about 189 m width and 251 m length constructed by the frame top-down method (FTDM) in the soft clay region in the Shanghai metropolitan area. The field monitoring results indicate that the magnitudes of wall deflections and ground settlements, along with the column’s uplift difference, are relatively small, which are below the specified protection levels, and that the FTDM is feasible as one of the extralarge excavation construction methods. It is reasonable to predict wall deflection by 3D FEM simulation with qualitative comparison between the simulated column uplifts and the measured data, yet the prediction of the settlement distribution is of no satisfaction. This project studied in this paper not only serves as a special case study calibrated and verified by numerical tools but also provides insights into the design and construction of an extralarge deep excavation using the frame top-down method in soft soils and metropolitan environment.